Components of frontal assessment battery and clinical features in patients with stroke - Katsuya Sakai; Yuichiro Hosoi; Yusuke Harada; Yuichi Kato; Takayuki Miyauchi (Journal of Rehabilitation Medicine)
Objective: First, to investigate whether the 6 aspects of executive functions assessed by the Frontal Assessment Battery have different components and, if so, to extract those components using principal component analysis. Second, to identify patient groups based on their characteristics using cluster analysis.